Helicopter Logging Method for Reduced Impact Timber Harvesting Operations* - Akay, Abdullah E.; Bilici, Ebru (Forest Engineering and Technologies Platform, 2016)
Traditional timber harvesting methods can result in serious impacts on vegetation structures, soil properties, and biodiversity in forested areas. Helicopter logging provides important advantages of implementing environmentally friendly harvesting techniques. However, the cost of helicopter logging can be much higher than that of ground-based logging due to high equipment costs, maintenance costs, the cost of flight crew, and fuel costs. Thus, the helicopter logging operation should be carefully planned to implement cost effective and environmentally friendly logging operations. In this study, the stages of helicopter logging and operational factors were first described, and then the operation cost, environmental concerns, and safety practices in helicopter logging were discussed. It can be concluded that the helicopter logging can be effectively used for extraction of timbers especially from environmentally sensitive areas where road construction and logging operations are restricted. In fact, helicopter logging may be the only option to solve timber extraction problems in difficult terrains with steep slope.
Keywords: Engineering; Mühendislik